2021
DOI: 10.1111/dgd.12750
|View full text |Cite
|
Sign up to set email alerts
|

The developmental hourglass model is applicable to the spinal cord based on single‐cell transcriptomes and non‐conserved cis‐regulatory elements

Abstract: The developmental hourglass model predicts that embryonic morphology is most conserved at the mid‐embryonic stage and diverges at the early and late stages. To date, this model has been verified by examining the anatomical features or gene expression profiles at the whole embryonic level. Here, by data mining approach utilizing multiple genomic and transcriptomic datasets from different species in combination, and by experimental validation, we demonstrate that the hourglass model is also applicable to a reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…The requirement of both Lhx2/9 and Nhlh1/2 for Robo3 expression in dI1 neurons suggests that the two groups of TFs may cooperate to achieve Robo3 activation possibly via binding to their respective cis-regulatory regions on the Robo3 genomic locus. A recent study identified an enhancer element 20 kb upstream of the Robo3 transcriptional start site that is conserved across vertebrates ( 63 ). They showed that a reporter gene expression driven by this enhancer element in chick spinal cord overlap with Robo3 expression and also overlap with Lhx1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of both Lhx2/9 and Nhlh1/2 for Robo3 expression in dI1 neurons suggests that the two groups of TFs may cooperate to achieve Robo3 activation possibly via binding to their respective cis-regulatory regions on the Robo3 genomic locus. A recent study identified an enhancer element 20 kb upstream of the Robo3 transcriptional start site that is conserved across vertebrates ( 63 ). They showed that a reporter gene expression driven by this enhancer element in chick spinal cord overlap with Robo3 expression and also overlap with Lhx1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies will be important for understanding the relationship between gene expression and these divergent functions. Toward this end, recent studies have shown that V3 neurons in mice and zebrafish are molecularly heterogeneous ( Mukaigasa et al, 2021 ). This raises the possibility that these molecular subdivisions may, in mice, delineate the known anatomical and functional differences between subpopulations and, in zebrafish, define diverse, as of yet unknown, subpopulations for movement pattern generation.…”
Section: V3 Excitatory Neuronsmentioning
confidence: 99%